GENERATION Z CONSUMER PREFERENCES FOR INDONESIAN CUISINE IN SOUTH KOREA (QUANTITATIVE SURVEY ON PREFERENCES OF INDONESIAN CUISINE IN DAEJEON, SOUTH KOREA) - Juliana, Juliana; Eva Amalia; Heri Nuryanto (Media Bina Ilmiah, 2024)
This study aims to determine the level of preference of Generation Z for Indonesian food in the city of Daejeon, South Korea which was reviewed from the aspects of taste, price, and ease of obtaining. The research method used in this research is the descriptive quantitative method and the data is in the form of numbers generated from the actual situation. For the results: The highest like for Indonesian food is Soto. Based on the results of the test of Homogeneity of Variances it can be concluded that the Indonesian food Bakso, Nasi Goreng, Rendang, Sate, and Soto that the researchers compared are the same (homogeneous). Based on the ANOVA results it can be concluded that the Indonesian food Bakso, Nasi Goreng, Rendang, Sate, and Soto that the researchers compared had the same average. Based on the ANOVA results it can be concluded that the Indonesian food Bakso, Nasi Goreng, Rendang, Sate, and Soto that the researchers compared has a different average.